PENAL MEDIATION OF TREATMENTS FOR CHILDREN IN THE JUVENILE JUSTICE SYSTEM - Irma Cahyaningtyas (Fakultas Hukum, Universitas Diponegoro, 2018)
The protection of children becomes the responsibility of all parties, namely family, community and government. Indonesia through the Act No. 11 Year 2012 on Juvenile Justice System provides protection namely diversion which should be emphasized as a penal mediation which can be used to solve a juvenile cases. There are two main problems; firstly, how is the penal mediation process in the juvenile justice system; secondly, how is the implementation of the penal mediation which is based on Pancasila? The research method used in this paper was normative juridical research method. The approach used in this study is socio legal approach and the data analysis method used a qualitative analysis. The results that in penal mediation in the juvenile cases namely diversion aims to achieve restorative justice. The diversion process is very important and must involve the parties in order the mediation be effective. This process is what distinguishes from the treatments of juvenile’s cases before Act No. 11 Year 2012. In the previous times, penal mediation was not acknowledged so law enforcement procedure is always ends at Juvenile court. Penal mediation in juvenile justice system must be based on Pancasila as the philosophical foundation of Indonesia, which means diversion process must be in accordance with the values of Pancasila, which are are religious moral values; humanistic values; nationalistic values, democratic, and social justice.